Effective Problem Based Learning (PBL) Based Local Materials for Improving Metacognition Skills, Inquiry Skills and Social Skills Class VIII SMP Pawyatan Daha 2 Kediri - Siti Lailatus Sa’adah; Mochammad Ardian Suryaji; Shilvi Nur Azizah; Poppy Rahmatika Primandiri; Agus Muji Santoso (Universitas Sebelas Maret, 2015)
Learning in the SMP Pawyatan Daha 2 Kediri with multistrategi. This condition causes the social interaction of students, students' awareness in solving the problem and apply the concepts learned in the real world are underdeveloped. In response to these problems applied learning model based PBL local materials. The expected application of the model is more active students to inquire and interact actively to the problems around them, causing a deep impression in learning. This study aims to determine the effectiveness of PBL model’s local materials based to metacognition skills, inquiry skills and social skills and eighth grade students of SMP Pawiyatan Daha 2 Kediri. This study is a quasi experimental design with non-equivalent control group design that uses the class as a control (multistrategi) and one class as the experiment (PBL). Used several instruments to support this research that metacognition skills measurement using metacognition skills assessment rubric in the form of pretest and posttest are integrated on cognitive achievement test, measuring inquiry skills such as observation sheets, measuring social skills of students in the form of a questionnaire. Data metacognition skills and inquiry skills were tabulated and analyzed using SPSS 16 for windows parametric t-test analysis and social skills using descriptive analysis. This study shows that: (1) there are differences posttest in metacognition skills in the experimental class and control class (t.hit = 2.501> 2.00665), (2) with a control group of inquiry skills experiment (t.hit = 3.130> 2.00665), (3) social skills showed that the experimental class better than the control class. It was concluded that the model PBL locally based material (utilizing the materials and tools around the student) is effective for improving metacognition skills, inquiry skills and social skills class VIII SMP Pawyatan Daha 2 Kediri.Keywords: Problem-based learning, metacognition skills, inquiry skills, social skills